Look out highway [compact disc] - Musselwhite, Charlie (Forty Below Records, 2025)
"Charlie Musselwhite is an American icon. His story is entangled in the story of America, and he's been tracing it's highways and entertaining it's audiences, and those abroad, for nearly six decades. So, it's fitting that his new record, is entitled as it is, and it's remarkable that a man who has spent more days on the road than off still brings such spirit and passion to the music and the lifestyle." --www.cvsmidwesttape.ca.